The student's guide to Shakespeare - McKenzie, William, 1976- (Edinburgh University Press, 2017)
"This book is a 'one-stop-shop' for the busy undergraduate studying Shakespeare. Offering detailed guidance to the plays most often taught on undergraduate courses, the volume targets the topics tutors choose for essay questions and is organized to help students find the information they need quickly. Each text discussion contains sections on sources, characters, performance, themes, language, and critical history, helping students identify the different ways of approaching a text. The book's unique play-based structure and character-center approach allows students to easily navigate the material. The flexibility of the design allows students to either read cover-to-cover, target a specific play, or explore elements of a narrative unit such as imagery or characterization. The reader will gain quickly a full grasp of the kind of dramatist William Shakespeare was - and is."--